Thermal conductivity of supraglacial volcanic deposits in Iceland - Möller, Rebecca; Römer, Wolfgang; Möller, Marco; Wollenberg, Uwe; Lehmkuhl, Frank; Schneider, Christoph; Kukla, Peter (RWTH Aachen University, 2020)
International journal of earth sciences 109(2), 569-585 (2020). doi:10.1007/s00531-020-01820-0 : Published by Springer, Berlin